Differences in the pathogenetic characteristics of prostate cancer in the transitional and peripheral zones and the possible molecular biological mechanisms - Yu, Xudong; Liu, Ruijia; Song, Lianying; Gao, Wenfeng; Wang, Xuyun; Zhang, Yaosheng (Frontiers in Oncology, 2023)
Since the theory of modern anatomical partitioning of the prostate was proposed, the differences in the incidence and pathological parameters of prostate cancer between peripheral zone and transition zone have been gradually revealed. This suggests differences in pathogenic pathways and molecular biology between prostate cancer zones. Over the past decade, advances in sequencing technologies have revealed more about molecules, genomes, and cell types specific to the peripheral and transitional zones. In recent years, the innovation of spatial imaging and multiple parameter magnetic resonance imaging has provided new technical support for the zonal study of prostate cancer. In this work, we reviewed all the research results and the latest research progress in the study of prostate cancer zones in the past two decades. We summarized and proposed several key issues and focused directions for understanding the differences between peripheral and transitional zones in prostate cancer.